Improving adherence to echocardiogram reporting guidelines in patients with repaired tetralogy of fallot: A quality improvement initiative. Issue 4 (17th March 2021) - Srnka, Charlotte M.; Strohacker, Courtney M.; Balasubramanian, Sowmya; Yu, Sunkyung; Lowery, Ray; Lu, Jimmy C.
Abstract: Background: In patients with repaired tetralogy of Fallot (TOF), key echocardiogram report elements have been identified, but poor adherence has been demonstrated, particularly for quantitative assessment. We report a quality improvement effort to improve adherence at our institution, with a focus on increasing quantitative assessment of right ventricular (RV) function. Methods: Baseline compliance was established by a 3‐month retrospective review of outpatient echocardiogram reports. Intervention 1 included presenting baseline data and reviewing the guidelines with echocardiogram laboratory staff (physicians and sonographers). Intervention 2, chosen to focus on quantitative assessment of RV function, involved recommending measurement of tricuspid annular plane systolic excursion (TAPSE) for all echocardiograms. Reporting rates were prospectively analyzed for 1 month after each intervention. To evaluate sonographer versus physician compliance, both study images (acquisition of TAPSE images) and reports were reviewed. Results: At baseline, adherence was poor (median 65% of elements reported), with lower rates for measurements versus descriptive elements (median 40% vs 78%, p<.0001). Following intervention 1, total reported elements improved (median 71% vs 65%, p=0.02) due to increase in measurements (median 50% vs 40%, p=0.02). Reports of quantitative RV function did not significantly change after either intervention, but sonographer compliance improved after intervention 1 (33% vs 14%, p=0.03), with further improvement after intervention 2 (53% vs 14%, p=0.001). Conclusion: While education on lesion‐specific guidelines may modestly improve adherence, standardization has a greater effect. However, interventions may have differential impact on sonographers versus attendings, and iterative interventions may be required to change practice patterns.